Analyzing the Students’ Academic Writing Project Using Thematic Progression - Fatmawati, Ayu; Haryanti, Dhena Usthiana (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2025)
This study analyzed students’ academic writing projects using thematic progression analysis. The investigation aimed to identify the thematic progression development patterns commonly used in students’ writing projects and to understand how these patterns relate to overall writing quality. Using the qualitative method, this study described the analysis of student’s writing projects from the thematic progression point of view. The data of the study were six writing projects, which were analyzed and categorized into some patterns so that the level of coherence could be seen. As the result, the data of writing projects showed that they used three dominant patterns, namely reiteration, multiple, and zig-zag. The second discovery found that all of the academic papers were categorized as less coherent, indicating that the respondent often introduced new themes in the middle of paragraphs, disrupting the flow of ideas and making it difficult for readers to follow the main argument. After conducting the research, researchers suggested that lecturers should strengthen students’ ability to develop coherent paragraphs by providing explicit instruction on thematic progression patterns, encouraging students to practice various patterns, and providing feedback on the coherence of their writing.